A raiz da mandioca enquanto elemento cultural da culinaria na comunidade quilombola lagoa da pedra - Moura, Karinny Silvia Vieria de (Universidade Federal do Tocantins, 2021)
The idea of this work is the Inventory of a regional product as a cultural element of the Quilombola community Lagoa da Pedra located 3km from the town of Canabrava, municipality of Arraias, Tocantins. This research, therefore, consists in the identification and survey of the traditional knowledge and practices existing in the cultural gastronomic manifestations found in the quilombola community, having cassava root as the main reference of local cuisine. In the village, cassava is commonly cultivated and appreciated by residents of the region, as well as one of the main sources of food used in the traditional cuisine of the community. In addition, the work develops from the practices and research carried out in the “Projeto Gosto” project, an extension project of the discipline of Gastronomy Management and Culture offered in the course of Heritage and Socio-Environmental Tourism at the Federal University of Tocantins. This research is characterized by bibliographic research, with a qualitative approach. The data collection instrument consisted of two tools, the first being an interview script with (open) questions and the IRGC Inventory form (Inventory of Cultural Gastronomic References) method that proposes alternatives for preserving traditional gastronomic knowledge. The inhabitants of the quilombola community Lagoa da Pedra, according to the data collected, declared cassava root an element of cultural gastronomic value for the community.